2003
DOI: 10.1007/s00253-002-1202-6
|View full text |Cite
|
Sign up to set email alerts
|

Global metabolic regulation analysis for Escherichia coli K12 based on protein expression by 2-dimensional electrophoresis and enzyme activity measurement

Abstract: Regulation of the main metabolic pathways of Escherichia coli K12 was investigated based on 2-dimensional electrophoresis (2DE) and the measurement of enzyme activities. The cells were grown aerobically in different carbon sources, such as glucose, acetate, gluconate or glycerol. Microaerobic cultivation was also conducted with glucose as a carbon source. Fifty-two proteins could be identified based on 2DE, and 26 enzyme activities from the main metabolic pathways-including glycolysis, pentose phosphate pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
134
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(145 citation statements)
references
References 44 publications
11
134
0
Order By: Relevance
“…1). Not surprisingly, this behavior correlates inversely with that of the TCA cycle, which becomes repressed during growth on D-glucose (6,320,342) and induced during growth on acetate (226,329,342).…”
Section: Recycling Coenzyme Amentioning
confidence: 95%
See 1 more Smart Citation
“…1). Not surprisingly, this behavior correlates inversely with that of the TCA cycle, which becomes repressed during growth on D-glucose (6,320,342) and induced during growth on acetate (226,329,342).…”
Section: Recycling Coenzyme Amentioning
confidence: 95%
“…3) (6,160,420). In the absence of oxygen and under conditions that favor catabolite repression (e.g., excess glucose), E. coli cells do not induce the full TCA cycle (6,320,342). Instead, they operate a branched version, which forms succinyl-CoA by a reductive pathway and 2-ketoglutarate by an oxidative one (100,168,282,420).…”
Section: Limiting the Tricarboxylic Acid Cyclementioning
confidence: 99%
“…Although studies have demonstrated that in vitro measured enzymatic activity do not obligatorily correlate with in vivo metabolic fluxes [21], enzyme activity can provide some information about metabolic changes. The lower activities of PFK and ICDH under oxidative condition than that in the control group indicated that PFK and ICDH were allosterically inhibited by higher metabolites concentrations in EMP and TCA under oxidative condition [22]. Metabolites measurement certified the enzyme activity result.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the amount of protein is not always proportional to the protein activity, which in turn does not necessarily correlate with the corresponding metabolic reaction rate. However, it has been reported that protein abundance data obtained from proteome profiles appear to correlate to some extent with the enzyme activities in E. coli, with a few exceptions (231). Thus, it appears as though proteomics can be effectively used to identify candidates for successful metabolic engineering for improved bioproduct yield.…”
Section: Proteomics For Biotechnologymentioning
confidence: 99%